Boomerons in a 1-D lattice with only nearest-neighbor interactions. (2nd November 2020) - Katz, Shmuel; Givli, Sefi
Abstract: We report on the existence of boomerons in a 1-D periodic lattice with no on-site potentials. Following an impact, a spatially localized wave phenomenon forms. This envelope wave packet, with frequency within the propagating band of small-amplitude waves, propagates into the chain, decelerates, and reverses direction without any external forcing. Our results show that this remarkable response requires the nearest-neighbor interactions to have non-convex potential with a branch of negative stiffness. It is suggested that the reversing motion is a consequence of the intriguing interaction between the localized phenomenon and the trail of nonlinear waves behind it.